ARE SWIMMERS AND CYCLISTS DIFFERING EACH OTHER ON THE BASIS OF SELECTED PHYSIOLOGICAL VARIABLES? – A JUXTAPOSITION ANALYSIS (International Journal of Food and Nutritional Sciences, 2022)
The goal of the study being presented is to determine the physiological differences between cyclists and swimmers. Thirty swimmers and thirty cyclists, all national athletes from various Indian states, were included in the research investigation. They are between the ages of 18 and 28yrs.The data were evaluated using an oximeter for oxygen saturation analysis, vital capacity by dry spirometer, and fat % and BMI by Omron body composition monitor. These data were collected from the Indian national swimming and cycling competitions in Bangalore in 2021 and Senior National in Mumbai 2021 India, respectively.The mean and standard deviation among swimmers and cyclists were determined by performing descriptive statistics and for further analysis an independent T-test employed on the obtained data. The degree of significance was fixed at 0.05 to test the hypothesis. IBM SPSS 20 Version statistical programs for social science were used to perform the statistical analysis. As per the research findings, t-statistics are significant for oxygen saturation, with the exception of BMI, fat percentage, and vital capacity, where the P value is more than 0.05. According to this research study, outcome states that there is a considerable difference in oxygen saturation between swimmers and cyclists, although there is insignificant difference in BMI, fat percentage, and vital capacity between the both sports, it concludes that the swimmers are having a significant difference than cyclist for oxygen saturation except in BMI, vital capacity & fat percentage. Therefore, the null hypothesis is failed to reject in BMI, vital capacity and fat % whereas in regard of oxygen saturation the null hypotheses is failed to accept.